Changing regulation of clinical trials in Europe. Issue 4 (July 2010) - Davis, Brian
The lack of harmonization of legislation, guidance and procedures for conducting clinical trials in Europe is generally considered unsatisfactory, despite the implementation of the Clinical Trials Directive in 2004. This article outlines the measures being taken by the Clinical Trials Facilitation Group of the Heads of Medicines Agencies and the Ad Hoc Clinical Trials Group of the European Commission to improve authorization, amendment and safety monitoring for clinical trials. It also comments, from a UK perspective, on the current status of the Commission''s consultation and impact assessment on potential changes to the Clinical Trials Directive, and anticipates the likely changes in the next 5 years.